Insights Into Landscape-Scale Actions: Lessons from the Riau Landscape Program, Indonesia - Angeline Gloria; Yudo Anggoro (CV. Literasi Indonesia, 2025)
In recent decades, the world has faced increasing socio-environmental risks due to record-breaking global temperatures driven by climate change. These impacts, ranging from extreme weather, prolonged droughts, and biodiversity loss to food insecurity, displacement, and economic disruption, are expected to intensify without effective mitigation. One response is the landscape approach, promoting multi-stakeholder collaboration to balance commodity production, forest conservation, sustainable livelihoods, and community well-being. This study examines the successes, challenges, and lessons from Phase 1 (2021–2025) of the Riau Landscape Program by Earthworm Foundation and provides strategic recommendations to strengthen Phase 2 (2026–2030). Using a qualitative case study approach including semi-structured interviews, focus group discussions, and document review, the study identifies four key themes influencing implementation: program design and delivery, institutional and policy support, multi-stakeholder engagement, and internal governance and capacity. Applying the Five E’s Framework for effective landscape implementation, the study proposes five strategic recommendations: (1) evaluating progress and learning from Phase 1, (2) strengthening governance by clarifying roles and improving systems, (3) adopting adaptive, phased approaches, (4) engaging stakeholders to scale impact and align with policy, and (5) fostering dynamic processes with risk management and iterative learning. The study also highlights future research opportunities, including assessing landscape approach impacts on corporate supply chains and exploring innovative financing mechanisms such as blended finance, green bonds, and carbon credits within the Indonesian context. These findings contribute to the advancement of integrated landscape approaches that align environmental sustainability with inclusive economic development.